Ngoma : discourses of healing in central and southern Africa - Janzen, John M. (Comparative studies of health systems and medical care., 1992)
Drawing on his recent field research in Kinshasa, Dar-es-Salaam, Mbabane, and Capetown, Janzen reveals how ngoma transcends national and social boundaries.